Randomized Controlled Trial of Inner Resources Meditation for Family Dementia Caregivers. Issue 12 (6th March 2017) - Waelde, Lynn C.; Meyer, Hilary; Thompson, Jason M.; Thompson, Larry; Gallagher‐Thompson, Dolores
Abstract : Objective: This randomized controlled trial examined the comparative effectiveness of 2 interventions for improving diurnal cortisol slope and life satisfaction and reducing stress symptoms among older female dementia family caregivers. Method: Thirty‐one family dementia caregivers were randomized to 8 weeks of Inner Resources for Stress mindfulness meditation and mantra training (IR) or psychoeducation and telephone support (PTS). Results: Intention‐to‐treat analyses revealed statistically significant pre‐post improvements in diurnal cortisol slope and overall life satisfaction, but not depression or self‐efficacy, in the IR relative to the PTS group. Adherence to between‐session meditation practice was significantly associated with decreases in depression and self‐reported improvements in ability to cope with stress. In addition, IR participants rated the overall benefits of the program more highly than the PTS group. Conclusion: These results indicate that mindfulness meditation and mantra has promise as a feasible and effective caregiver intervention for quality of life and physiological responding to stress.